Fermented jellyfish (Rhopilema esculentum) collagen enhances antioxidant activity and cartilage protection on surgically induced osteoarthritis in obese rats - Sudirman, Sabri; Chen, Chun-Yu; Chen, Chun-Kai; Felim, Jerrell; Kuo, Hsiang-Ping; Kong, Zwe-Ling (Frontiers in Pharmacology, 2023)
Collagen has been considered a key treatment option to prevent damage to the articular cartilage over time and support the healing process following the onset of osteoarthritis (OA). This study aimed to investigate the effect of collagen fermented from jellyfish (FJC) by Bacillus subtilis natto on anterior cruciate ligament transection with medial meniscectomy (ACLT+ MMx) induced knee OA in high-fat diet (HFD) induced obesity rat. The male Sprague–Dawley rats were fed an HFD for 6 weeks before ACLT+ MMx surgery, after which they were administered a daily oral gavage of saline (Control, OA, OBOA), either with FJC (20, 40, and 100 mg/kg body weight) or glucosamine sulfate as a positive control (GS; 200 mg/kg body weight) for 6 weeks. Treatment with FJC decreased the fat weight, triglyceride, and total cholesterol levels in obesity rats. Additionally, FJC downregulated the expression of some proinflammatory cytokines, including tumor necrosis factor-α, cyclooxygenase-2, and nitric oxide; suppressed leptin and adiponectin expression; and attenuated cartilage degradation. It also decreased the activities of matrix metalloproteinase (MMP)-1 and MMP-3. These results demonstrated that FJC showed a protective effect on articular cartilage and also suppressed the degradation of cartilage in an animal OA model, suggesting its potential efficacy as a promising candidate for OA treatment.